Japan's Low Inflation from a Quantity Theory Perspective - Gunther Schnabl; Taiki Murai (CESifo GmbH, 2024)
The paper examines the relationship between money and prices in Japan based on Fisher's (1911) transactions version of the quantity theory of money. Money is defined as aggregate debt less net foreign assets. A general price index is constructed from consumer prices, real estate prices, stock prices, nominal wages and the nominal effective exchange rate. Evidence shows a high correlation between money growth and general price inflation for Japan from 1980 to 2022, supporting the view that inflation is a monetary phenomenon. The paper argues that Japan's inflation has remained low since the 1990s because the policy mix of monetary and fiscal expansion led to the fall of private debt and the rise of government debt, resulting in a low money growth at the aggregate level. An exit from monetary and fiscal expansion would contribute to the recovery of private debt creation, which would restore the money, price and growth dynamics in Japan.
Keywords: E31; E52; 330; quantity theory of money; inflation; monetary policy